Factors Related to Stunting In Toddlers Aged 25-59 Months In Posyandu Bontonyeleng Health Center Area - Andi Nurlaily; Andi Tenri Fajriani; Ely Kurniati; Sri Eka Juniarly (Jurnal Life Birth, 2021)
Stunting is still a problem in nutrition and child development problems in Indonesia. Stunting in South Sulawesi in 2019 amounted to 11.4%. The highest stunting prevalence is in the Bulukumba Regency, which is as much as 7.7% of short toddlers and 23.3% of very short toddlers. It is known the factors associated with the occurrence of stunting. The study was observational with a case-control design using secondary data from the mother's KIA book and primary data through interviews. Variables studied included the mother's height, the mother's education level, economic status, exclusive breastfeeding, birth weight, and gender. Sampling technique using simple random sampling. The number of samples in the study was 152 samples which included 76 case groups and 76 control groups. The results of the study obtained variables related to stunting events are maternal height p-value 0.015 (95% CI 1,495-40,012), exclusive breastfeeding p-value 0.006 (95% CI 1,366 - 6,228), sex p-value 0.002 (95% CI 1,590-7,312). The results of the multivariate analysis of maternal height had the highest risk of stunting incidence (p=0.015 OR=7,735, 95% CI=1,495-40,012) and gender was the most significant factor in stunting p-value events of 0.002 (95% CI 1,590-7,312). Maternal height is the most dominant factor in relation to stunting events.